Hacia un Marco Conceptual Común sobre Trazabilidad en la Cadena de Suministro de Alimentos - Rincón Ballesteros, Dora Lucia; Fonseca Ramírez, Johan Esteban; Orjuela-Castro, Javier Arturo (Ingeniería, 2017)
Abstract Background: The absence of a common conceptual framework on traceability in the food supply chain (SCF), prevents a cohesive development of this concept. The absence has generated confusion and has made it impossible to demonstrate the social and commercial advantages of its implementation. In addition, not having a common framework in countries such as Colombia obstructs the development of public policies. Method: A systematic review of the literature was carried out in four stages: search protocol to consult articles in the databases Scopus, Science Direct and ISI Web; review and selection of relevant articles; extraction and incorporation of data into tables and formats designed for this purpose and elaboration of the conceptual framework. Results: A common conceptual framework is proposed for the design and implementation of a traceability system in the SCF covering the following aspects: definition of traceability, characteristics and properties, schemes, traceable resource unit, motivators and recording systems. The international and national legislation is evaluated and aspects for its incorporation are established. The proposed conceptual framework is exemplified by the meat supply chain to guide the implementation of traceability systems in CSA in Colombia. Conclusions: The conceptual framework for SCF traceability can be a guide for the implementation and development of food chains in the Colombian context. Implementing this in agricultural chains would allow the differentiation of origin, which can be a competitive factor for producers with good agricultural practices, as well as provide effective logistic capacities for all agents of the SCF. The effect of its implementation should be evaluated with special emphasis on the impact on brand positioning and the establishment of fair prices as an effect of tracking and tracing the traceability system. Language: Spanish.